2006
DOI: 10.1136/sti.2006.019992
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study assessing the effects of introducing the female condom in a sex worker population in Mombasa, Kenya

Abstract: Objective: To assess the impact and costs of adding female condoms to a male condom promotion and distribution peer education programme for sex workers in Mombasa, Kenya. Design: A 12 month, prospective study of 210 female sex workers. Methods: We interviewed participants about their sexual behaviour every 2 months for a total of seven times and introduced female condoms after the third interview. We also collected cost data and calculated the cost and cost effectiveness of adding the female condom component t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 16 publications
(8 reference statements)
3
61
0
Order By: Relevance
“…Although the male partner is not unaware of the female condom, it does provide a prevention strategy that is less dependent on male willingness. Cost and mechanical difficulties have been cited as reasons for limited uptake (Galvao et al 2005), but newer designs are easier to use, can be reused (Thomsen et al 2006), and are made of materials that improve sensation with the promise of enhancing acceptability, uptake, and cost (Coffey et al 2006). There are increasing reports of female condoms being used for HIV prevention in anal sex (http://doh.dc.gov/doh/cwp/ view,a,1371,q,602647,dohNav_GID,1839,doh Nav, |33815|,,.asp).…”
Section: The Female Condommentioning
confidence: 99%
“…Although the male partner is not unaware of the female condom, it does provide a prevention strategy that is less dependent on male willingness. Cost and mechanical difficulties have been cited as reasons for limited uptake (Galvao et al 2005), but newer designs are easier to use, can be reused (Thomsen et al 2006), and are made of materials that improve sensation with the promise of enhancing acceptability, uptake, and cost (Coffey et al 2006). There are increasing reports of female condoms being used for HIV prevention in anal sex (http://doh.dc.gov/doh/cwp/ view,a,1371,q,602647,dohNav_GID,1839,doh Nav, |33815|,,.asp).…”
Section: The Female Condommentioning
confidence: 99%
“…[15][16][17][18][19][20] Studies around the globe have found positive results from introducing FC to women of all ages, including decreased STI incidence and increased protected sex. 21,22 Despite extensive research showing its effectiveness and acceptability with various U.S. populations at highest risk, the FC remains unpopular and underutilized in most communities. 11 Cost is a contributing factor.…”
Section: Introductionmentioning
confidence: 99%
“…G. Williams et al, 2003) in consistent condom use. Increase in condom use for different FSW partner types was measured in some studies and consistent condom use was less with intimate partners of FSWs (boyfriends and non-paying regular partners) than with paying clients (Feldblum et al, 2005;Nagot et al, 2005;Ngugi et al, 2007;Odek et al, 2009;Raul et al, 2002;Ray et al, 2001;Steen et al, 2000;Thomsen et al, 2006;Wechsberg et al, 2006). Considerable loss to follow-up was reported in some of the studies with a few showing high attrition rates of greater than 50% (Feldblum et al, 2005;Ngugi et al, 2007;Ray et al, 2001;Walden et al, 1999;B.…”
Section: Effectivenessmentioning
confidence: 99%
“…Ten studies used peer education for delivery of condom use messages while six studies within the review used only health or programme staff for the delivery of condom use messages (Laga et al, 1994;Ray, van De Wijgert, Mason, Ndowa, & Maposhere, 2001;Steen et al, 2000;Thomsen et al, 2006;Walden, Mwangulube, & Makhumula-Nkhoma, 1999;Wechsberg, Luseno, Lam, Parry, & Morojele, 2006). Acceptability and increase in female condom use was measured in three of these studies in South Africa (Wechsberg et al, 2006), Zimbabwe (Ray et al, 2001) and Kenya (Thomsen et al, 2006) and these three studies showed increases in female condom use after the intervention. Acceptability and increased use of female condom were self-reported using structured questionnaires.…”
Section: Effectivenessmentioning
confidence: 99%